Memorable Tourism Experience (MTE) pada Wisata Gastronomi Menggunakan Konsep Ngidang di Palembang - Debby Fifi Yanti; Nurvia Nathasya; Alfitriani Alfitriani; Alip Suroto (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2026)
This study analyzes the transformation of the gastronomic tourism experience of the Ngidang tradition in Palembang City into a Memorable Tourism Experience (MTE) that lingers in tourists' long-term memory. Employing a qualitative descriptive-analytical approach with triangulation of in-depth interviews (48 participants), participant observation, and documentation, this study identifies seven dimensions of MTE (Kim, Ritchie, & McCormick, 2012) that are fully present in Ngidang: novelty (100%), knowledge (100%), hedonism (100%), meaningfulness (93%), local culture (90%), refreshment (87%), and involvement (83%). The findings reveal three mechanisms of collective memory formation: shared bodily practices that create somatic markers (Damasio, 1994), repetitive ritual structures (Connerton, 1989), and circular seating arrangements without hierarchy (Oldenburg, 1999). The study also identifies the unique role of the ngobeng as a cultural broker that reinforces cultural authenticity. Ngidang is proven to not only satisfy sensory aspects but also touch the spiritual and emotional dimensions of tourist